(untitled) (CIPEEX, 2025)
The digital age has generated significant impacts in several areas. In Law it was no different, specifically in Brazilian Electoral Law, which has undergone considerable changes due to technological advances. In the past, the rules were based on traditional practices, and challenges that previously did not exist today require special attention, as they can strongly influence the Brazilian electoral scenario, such as disinformation and the use of social media, which can directly impact voting. It is necessary to reflect on how the Brazilian legal system keeps pace with these changes and contributes to strengthening democracy. The present study aims to analyze the transition from traditional Electoral Law and the legal paths in the face of digital challenges, preserving democracy. The methodology used was bibliographic and documentary review, with emphasis on the Civil Rights Framework for the Internet (Law nº 12.965/2014) and the creation of the Integrated Center for Combating Disinformation and Defense of Democracy (CIEDDE). It was observed that, even with some advances in the regulation of the digital environment, there are still issues that need to be resolved, mainly regarding the supervision of online campaigns and the fight against “fake news,” which can compromise the structure of the Brazilian electoral system. In order to guarantee fair and transparent elections, it is clear that, in addition to strengthening institutions and political education, constant updating of electoral rules and efficient coordination between technology, law, and society are also required.